Glassy State Lead Tellurite Nanobelts: Synthesis and Properties - Liu Hong; Chen Xueyan; Wan Buyong; Hu Chenguo; Xi Yi; He Xiaoshan (Nanoscale Research Letters, 2010)
Abstract The lead tellurite nanobelts have been first synthesized in the composite molten salts (KNO3/LiNO3) method, which is cost-effective, one-step, easy to control, and performed at low-temperature and in ambient atmosphere. Scanning electron microscopy, X-ray diffraction, transmission electron microscopy, X-ray photoelectron spectrum, energy dispersive X-ray spectroscopy and FT-IR spectrum are used to characterize the structure, morphology, and composition of the samples. The results show that the as-synthesized products are amorphous and glassy nanobelts with widths of 200–300 nm and lengths up to tens of microns and the atomic ratio of Pb:Te:O is close to 1:1.5:4. Thermo-gravimetric analysis (TGA) and differential scanning calorimetry (DSC) and investigations of the corresponding structure and morphology change confirm that the nanobelts have low glass transition temperature and thermal stability. Optical diffuse reflectance spectrum indicates that the lead tellurite nanobelts have two optical gaps at ca. 3.72 eV and 4.12 eV. Photoluminescence (PL) spectrum and fluorescence imaging of the products exhibit a blue emission (round 480 nm).